Profil Interaksi Teman Sebaya pada Peserta Didik di Kelas XI SMA PGRI 4 Padang - Nurlaili Sepya; Ahmad Zaini; Wira Solina (Universitas PGRI SUMATERA BARAT, 2021)
ABSTRACT This research is motivated by the existence of students who are less able to interact with peers. The purpose of this study was to describe the profile of peer interaction of students in class XI High School PGRI 4 Padang seen from the following factors: 1) Imitation; 2) suggestion; 3) identification; 4) sympathy. This type of research is descriptive quantitative, the total population is 42 students and the whole sample is used as a research sample using the total sampling technique. The instrument used was a questionnaire. The data were analyzed using descriptive statistics using percentage techniques. This study revealed that the peer interaction profile of students was seen from the following factors: 1) Imitation was in a good category; 2) suggestions are in a good category; 3) identification is in the very good category; 4) sympathy is in the very good category. Keywords: students, peer interaction, imitation, suggestion, identification, sympathy ABSTRAKPenelitian ini dilatarbelakangi oleh adanya peserta didik yang kurang mampu dalam berinteraksi antar teman sebaya. Tujuan penelitian ini adalah untuk mendeskripsikan mengenai profil interaksi teman sebaya peserta didikdi kelas XI Sekolah Menengah Atas PGRI 4 Padang dilihat dari faktor: 1) Imitasi; 2) sugesti; 3) identifikasi; 4) simpati. Jenis penelitian ini adalah deskriptif kuantitatif, jumlah populasi 42 peserta didik dan keseluruhan dijadikan sampel penelitian dengan menggunakan teknik total sampling. Instrumen yang digunakan angket, Data dianalisis menggunakan statistik deskriptif teknik persentase. Penelitian ini mengungkapkan bahwa profil interaksi teman sebaya peserta didik dilihat dari faktor: 1) Imitasi berada pada kategori baik; 2) sugesti berada pada kategori baik; 3) identifikasi berada pada kategori sangat baik; 4) simpati berada pada kategori sangat baik. Kata Kunci : peserta didik, interaksi teman sebay, imitasi, sugesti, identifikasi, simpati